PERSEPSI PROFESI AKUNTAN TENTANG PENTINGNYA ETIKA DAN TANGGUNG JAWAB SOSIAL UNTUK PENCAPAIAN TUJUAN PERUSAHAAN - Mubarok, Abdulloh (PERMANA, 2010)
The research is aimed to know (1) how perception to accountant profession (lecturers, management accountants, students) abaut the interesting ethics and social responsibility to reach corporate goals. (2) are there significant difference to perception between each the accountant profession components. Perception between accountant profession abaut the interesting ethics and social responsibility to reach corporate goals is analyzed by comparing with the total of counting score to each component of respondents and the total of ideal score. Than it is interpreted by interpretation score cretaria. The difference of perception between each the accountant profession components is analyzed by Analysis of Variance (ANOVA) methods ( post hoc test ).The research show that commonly the accountant profession have good perception abaut the interesting ethics and social responsibility to reach corporate goals. From the third component, lecturer have the most good perception. Maybe, the lecturer not only teachs but also educates ethics. The studies also resumes that there is not siginificant difference to perception between each the accountant profession components (lecturers, management accountants, students). Keyword: perception, accountant profession, lecturers, management accountants, Students, ethics, social responsibility